CLASSROOM COMMUNICATION. AN INTERVENTION PLAN IN COMMUNICATION BOTTLENECKS - Ahmed KHALID (National Centre for Policy and Evaluation in Education, 2017)
Educational process requires an analysis and investigation of communication components, and in deep investigation of the communication in the classroom including interaction between students and teacher, sources of bottlenecks, the manner of expressing them and ways to optimize educational communication. Teaching communication efficiency is improved by several factors, of which, if they occur, may reduce differences what the teacher intends to provide to students and what they eventually capture or understand. These factors depend on the personality of the teacher, student personality, psychosocial and environmental context. Assuming that stronger influence of the teacher on students can be achieved by identifying and removing barriers to communication, the article aims to emphasize the origin of communication bottlenecks and propose a plan to improve communication in classroom.